2016
DOI: 10.18596/jotcsa.287337
|View full text |Cite
|
Sign up to set email alerts
|

Sorption study of methylene blue on activated carbon prepared from Jatropha curcas and Terminalia catappa seed coats

Abstract: This research work targets the effectiveness of the prepared activated carbon from Jatropha curcas and Terminalia catappa seed coats for adsorption of methylene blue (MB) from aqueous solution. The prepared Jatropha activated carbon (JAC) and Terminalia activated carbon (TAC) were characterised using Fourier Transform Infrared Spectroscopy (FTIR), Scanning electron microscopy (SEM), and Brunauer-Emmett-Teller (BET) surface area analysis. Effects of initial concentration, pH, contact time, adsorbent dose and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
3
6
0
1
Order By: Relevance
“…The results give a hint that chemisorption was the most favored mechanism in the uptake of the adsorbate by the adsorbent. Similar trend in kinetics was highlighted for the sorption of methylene blue onto Terminalia catappa and Jatropha curcas seed coats activated carbon (24). (25).…”
Section: Kinetic Studiessupporting
confidence: 71%
“…The results give a hint that chemisorption was the most favored mechanism in the uptake of the adsorbate by the adsorbent. Similar trend in kinetics was highlighted for the sorption of methylene blue onto Terminalia catappa and Jatropha curcas seed coats activated carbon (24). (25).…”
Section: Kinetic Studiessupporting
confidence: 71%
“…The SEM micrograph of DSAC before adsorption (Figure 2a) showed that there are many pores available for adsorption of RhB compared to DPAC (Figure 2c) with uneven like stone rough surfaces due to activation by acid treatment (10,28). The SEM micrographs of the loaded DSAC and DPAC (Figure 2b & 2d) indicated that the surfaces have been covered by RhB dye molecules.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Many treatment methods had been put into consideration for the removal of dyestuff from wastewater such as oxidation (6), photochemical degradation (7), electrochemical degradation (8), and membrane separation (9). Though most of the aforementioned treatment methods for separating dyes from dye-containing wastewater have great limitations which include exorbitant, less effectiveness, production of toxic materials, and high energy demands (10). However, adsorption as a treatment technique employing activated carbon is immensely gaining worldwide acceptance for removing dyes and other organic pollutants from aqueous solutions owing to its ease of operation, low cost, simple design, and regeneration (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Atık sulardan renk giderimi için oksidasyon, iyon değiştirme [10], ozonlama, koagülasyon, flokülasyon [11], çöktürme ve adsorpsiyon yöntemleri kullanılmaktadır [12]. Bunların arasında adsorpsiyon basit, ekonomik ve verimli bir yöntem olması sebebi ile çok fazla tercih edilmektedir [13]. Atık sulardan adsorpsiyon yöntemi ile boyar madde uzaklaştırılmasında aktif karbon, sahip olduğu özellikleri sebebiyle en çok tercih edilen adsorbanlardan biridir.…”
Section: Introductionunclassified